High precision CA-ID-TIMS U-Pb zircon age for the “Dueling Dinosaurs” locality, with implications for regional correlation, basal age and duration of the Hell Creek Formation, Montana - Eric M. Roberts; Marc S. Hendrix; Jahandar Ramezani; William C. Clyde; Pierre Zippi; Stuart Hodgson; Valerie Yuleridge; Lindsay E. Zanno (PLoS ONE, 2026)
Discovery of the “Dueling Dinosaurs” and other significant dinosaur localities from remote and isolated exposures of the Hell Creek Formation in central Montana highlight the complexity of establishing stratigraphic context and correlating Hell Creek Formation fossil localities located within and outside of the type area. Stratigraphic correlation is particularly problematic for the lower two-thirds of the Hell Creek Formation, which generally lacks reliable biostratigraphic or magnetostratigraphic zonation and has no dated ash beds. To address these enduring issues for one of the most significant Upper Cretaceous terrestrial fossil-bearing units in North America, detailed stratigraphic sections were established on the Murray Ranch and on McGinnis Butte in central Montana and correlated with other published Hell Creek Formation localities via magnetostratigraphy, biostratigraphy, and radioisotopic dating of ash beds. Results indicate that the K-Pg boundary is not exposed in the study area; however, high-precision U-Pb CA-TIMS zircon ages for two newly discovered ash beds (66.929 ± 0.020 Ma and 66.850 ± 0.026 Ma, 2σ internal uncertainties) that bracket the “Dueling Dinosaurs” quarry provide the first absolute ages for the lower portion of the Hell Creek Formation anywhere. Bayesian age-stratigraphic modelling places the “Dueling Dinosaurs” depositional age at 66.897 + 0.023/-0.028 Ma and suggests that the age of the base of the formation is ~ 67.102 + 0.710/-0.173 Ma (or older) in the study area. Comparison of stratigraphic architecture within the study area with published sections in the type area suggests that named sandstone marker horizons used for lithostratigraphic and sequence stratigraphic correlation in the type area have limited utility for regional correlation and need to be used with caution.